ENTREPRENEURIAL SUCCESS FACTOR ANALYSIS OF INTERNAL INTEREST IN ENTREPRENEURSHIP - Rahma Faelasofi (Saburai International Journal of Social Sciences and Development, 2018)
This study aims to analyze the internal factors of entrepreneurial success in Tulungagung village. Attempts to analyze the internal factors of entrepreneurial success is to determine the influence of the variables studied are expected to provide the right advice to help boost the economy in the village of Tulungagung. The method in this study using a sampling method. This research is a quantitative study, samples were taken from existing research subject population. The data used in this study are primary data. The subjects were processed bamboo craftsman entrepreneur who produces household appliances. Techniques of data retrieval is done through questionnaires and interviews. Results from this research that there is a partial correlation of the variable motivation, experience or knowledge, as well as the personality of the interest in entrepreneurship. Simultaneously shows the correlation of the variable motivation, experience or knowledge, as well as personality, against the 47.5% interest in entrepreneurship while the rest influenced by other variables. Partial hypothesis testing showed that of the three independent variables, only variables that affect a significant personality of the interest in entrepreneurship.